VALUASI JASA LINGKUNGAN HIDROLOGIS HUTAN PRODUKSI DESA LAKOMEA KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Safril Kasim; La ode Midi; Juliana Juliana (Universitas Haluoleo, 2015)
The study aimed to identify the total volume of clean water consumption and total economic value of hydrological services used for domestic and agricultura needs. The research was carried out in Lakomea Village, Landono District of South Konawe Regency since May to June 2015. The study employeed survey and depth interview with key respondents. Location of the study was determined using Purposive Sampling Method. While respondents were identified in the two stages : (1) Respondents are grouped in the two major gorups using Stratified Sampling Method namely: (a) Domestic water user group; and (b) Irrigation water consumers group. (2) Respondents for the domestic water users were then determined using Simple Random Sampling, whereas for irrigation water consumersusing Sensus Sampling Method with consideration that the number of users of irrigation water were only 3 families. Data analysis was conducted using Hedonic Price for water domestic used and Productivity Method for the agricultural used.The results of the research showed that the total volume of water usage over the past year using by135 families obtained 27.504 m3/year. While the economic value of this domestic waterused reached Rp. 16.197.930,72/year. The research also revealed that the economic irrigation water for rice fields achieved Rp. 1.811.950,00/Planting Season. In conclusion, Total Economic Value of the hydrological environmental services of Lakomea Productive Forest Area of Landono District, South Konawe Regencyobtained Rp. 18.009.880,72/year.Keywords: Valuation, Environmental Services, Domestic Use of Water, Agricultural Use of Water, Total Economic Value